Corneal Epithelial Thickness Profile in Healthy Portuguese Children by High-Definition Optical Coherence Tomography - Loureiro TO (Dove Medical Press, 2021)
Tomás de Oliveira Loureiro, Sandra Rodrigues-Barros, Diogo Lopes, Ana Rita Carreira, Filipe Gouveia-Moraes, Ana Vide-Escada, Nuno Patricio Campos Ophthalmology Department, Hospital Garcia de Orta, Almada, PortugalCorrespondence: Tomás de Oliveira LoureiroOphthalmology Department, Hospital Garcia de Orta, Avenida Torrado da Silva, Almada, 2805-267, PortugalTel +351 913 513 175Email loureiro.tomas@gmail.comIntroduction and Objective: To evaluate corneal epithelial thickness (ET) and corneal thickness (CT) profiles in healthy eyes of Portuguese children and provide information to establish the first normative Caucasian database for these age group.Methods: Sixty healthy eyes of 60 children aged between 8 and 18 were evaluated using the Cirrus high-definition optical coherence tomography device. The average ET and CT were assessed using Cirrus Review Software with predefined concentric corneal ring-shaped zones. Specific regions of ET (central, superior, inferior, temporal, nasal, superonasal, inferotemporal, superotemporal and inferonasal) were also assessed. The mean ET, the mean CT and the difference of ET in corresponding octants were compared by gender. Correlations between central epithelial thickness (CET), age and refractive error were evaluated.Results and Discussion: The average ET was lower in the peripheric zones, whereas the average CT was higher. ET was thinner in the superior area than in the inferior (p< 0.05). ET was thicker in boys than in girls (p< 0.05), but CT did not differ. CET was not correlated with older age or refractive error.Conclusion: Optical coherence tomography analysis of ET reveals that it is thinner in the periphery, where the CT is thicker. Unlike CT, ET seems to be influenced by gender. ET profile proved to be a useful tool in keratoconus diagnosis and subclinical keratoconus detection in adults. As epithelial changes occur early in the disease and keratoconus is more aggressive in pediatric population, a normative database of ET profile could contribute to enhance early recognition of the disease in this age group.Keywords: epithelial thickness, AS-OCT, keratoconus, children